2020
DOI: 10.1016/j.celrep.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Cell Resistance to EGFR and MET Inhibition Can Be Overcome via Blockade of FGFR-SPRY2 Bypass Signaling

Abstract: Highlights d Glioblastoma cells evade EGFR and MET inhibition via FGFR-SPRY2 bypass signaling d Autocrine FGFR signaling and SPRY2 synthesis explains heterogeneous drug response d FGFR blockade augments glioblastoma response to EGFR and MET inhibition d A bioluminescent reporter tracks longitudinal ERK response to therapy in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 55 publications
(57 reference statements)
1
28
0
Order By: Relevance
“…The EGFR-independent pathway may maintain stimulation of the PI3K-AKT signaling pathway. We and others previously reported an impact of integrin or JAK signaling in glioma intracellular signaling 55 , 56 , and other receptor tyrosine kinases 57 60 may be involved. Clark et al 57 demonstrated a compensatory activation of EGFR-related family members (ERBB2 and ERBB3) that enabled glioma stem cell proliferation, suggesting that simultaneous blockade of multiple ERBB family members may be required for more efficacious GBM therapy.…”
Section: Discussionmentioning
confidence: 70%
“…The EGFR-independent pathway may maintain stimulation of the PI3K-AKT signaling pathway. We and others previously reported an impact of integrin or JAK signaling in glioma intracellular signaling 55 , 56 , and other receptor tyrosine kinases 57 60 may be involved. Clark et al 57 demonstrated a compensatory activation of EGFR-related family members (ERBB2 and ERBB3) that enabled glioma stem cell proliferation, suggesting that simultaneous blockade of multiple ERBB family members may be required for more efficacious GBM therapy.…”
Section: Discussionmentioning
confidence: 70%
“…Direct repression of MAPKs MEK or ERK1/2 or the upstream activator Ras are associated with the emergence of resistance either by the reactivation of ERK1/2 through impaired repression or the activation of an alternative pathway [17] , [18] , [19] . One potential indirect repressor of ERK1/2 activation in tumor cells is dasatinib, a second-generation multitarget kinase inhibitor targeting both SRC and BCR-ABL kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Both the EGFR and FGFR signal transduction pathways are important in cancer, and the FGFR pathway is activated by EGFR-TKI treatment [ 11 ]. Therefore, the activation of the FGFR is likely to be another cause of resistance to EGFR-TKIs, and the combination of FGFR-TKIs and EGFR-TKIs is effective in glioblastoma and non-small cell lung cancer, as previously reported [ 42 , 43 ]. Since the FGFR mediates EGFR signaling, the efficacy of FGFR-TKIs in cancer treatment was investigated using C. elegans tumor models and lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 74%